Optimalisasi Potensi Usaha Berbasis Ekonomi Sirkular Melalui Pengelolaan Sampah Organik Dan Aplikasi Manajemen Usaha Bumdesa Rizqi Barokah Mandiri - Milzam, Muhammad; Hakim, Mujibul; Rakhmatika, Devi; Syaharani, Adinda Dwi Putri; Utomo, Arif Budi; Dinda, Shafa Aleeqa (Politeknik Indonusa Surakarta, 2025)
Organic waste management in rural areas continues to be a significant challenge with implications for both environmental quality and community health. Rejosari Timur Village, through Rizq Barokah Mandiri Village-Owned Enterprise (BUMDes), faces constraints such as weak managerial capacity, limited innovation in organic waste processing, and low digital integration. This community empowerment program was designed to overcome these issues by applying circular economy principles in organic waste management and strengthening business governance through a Management Information System (MIS). The program was carried out using a participatory approach in five stages: problem identification, MIS application development, training and risk management workshops, implementation of waste shredding technology and MIS, and monitoring and evaluation through baseline-endline measurement and pre-post tests. The results showed an improvement in the managerial capacity of BUMDes, particularly in sustainable financial planning, risk management, and digital marketing supported by Artificial Intelligence. The introduction of an organic waste shredder enabled the production of compost as a value-added agricultural product, while the MIS facilitated transparent and efficient transaction recording and cash flow monitoring. In conclusion, the integration of digital technology and circular economy-based waste processing proved effective in enhancing the competitiveness of BUMDes and promoting rural economic independence while preserving environmental sustainability.